2010
DOI: 10.1088/0741-3335/52/10/104002
|View full text |Cite
|
Sign up to set email alerts
|

Resistive wall mode control code maturity: progress and specific examples

Abstract: Two issues of the resistive wall mode (RWM) control code maturity are addressed: the inclusion of advanced mode damping physics beyond the ideal MHD description, and the possibility of taking into account the influence of 3D features of the conducting structures on the mode stability and control. Examples of formulations and computational results are given, using the MARS-F/K codes and the CarMa code. The MARS-K calculations for a DIII-D plasma shows that the fast ion contributions, which can give additional d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
59
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(61 citation statements)
references
References 30 publications
2
59
0
Order By: Relevance
“…15 Calculations with the "MARS-K" code of the RWM stability of a DIII-D equilibrium indicate that beam ions can have a large effect on stability. 16 In NSTX, we find that energetic particles are generally stabilizing and that a reduction of this particle population leads to reduced RWM stability. A correlation between energetic particle modes and RWM destabilization has been observed in JT-60U.…”
Section: Introductionmentioning
confidence: 74%
See 2 more Smart Citations
“…15 Calculations with the "MARS-K" code of the RWM stability of a DIII-D equilibrium indicate that beam ions can have a large effect on stability. 16 In NSTX, we find that energetic particles are generally stabilizing and that a reduction of this particle population leads to reduced RWM stability. A correlation between energetic particle modes and RWM destabilization has been observed in JT-60U.…”
Section: Introductionmentioning
confidence: 74%
“…However, it is possible that the kinetic effects of energetic particles could change somewhat. 16 Second, the RWM growth rate and real rotation frequency appear on both sides of the dispersion relation in Eq.…”
Section: A Perturbative Versus Self-consistent Approachesmentioning
confidence: 99%
See 1 more Smart Citation
“…The experimental results of DIII-D RWM onset condition have been analyzed with the MARS-K code, 38 using both perturbative and self-consistent approaches.…”
Section: Analysis With Mars-kmentioning
confidence: 99%
“…Ref. 17 showed that a new instability with small growth rate can be excited when the trapped EPs were taken into account in the RWM dispersion relation. However, the effect of the trapped EPs on the RWM has not been fully resolved, and could be crucial for the future tokamak devices.…”
Section: Introductionmentioning
confidence: 99%